Mengungkap Perspektif Kepuasan Pelanggan di SPBU Pertamina 34.167.12 - Sandra, Marcella; Safitri, Wahayyina; Osa, Hamida; Nurhalisah, Siti; Abdullah, Muhammad (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study aims to examine the impact of service quality and brand image on customer satisfaction. The method used is quantitative with a causal approach, involving respondents who are at least 17 years old and are regular customers of the station. The sampling was conducted using purposive sampling technique, with a sample size of 96 people, calculated using the Lemeshow formula. The research results show that service quality, particularly the empathy indicator, significantly affects customer satisfaction. However, the physical evidence indicator (employee appearance) needs to be improved to enhance customer satisfaction. Brand image also significantly affects customer satisfaction, with appropriate pricing being the dominant factor. Nevertheless, the brand's image and popularity need to be further improved. Customer satisfaction was found to be in good condition, but improvements are still needed in the willingness-to-recommend indicator. One of the recommendations is to activate a special program offering discounts for each fuel purchase above a certain amount, which can only be obtained by customers who refer their colleagues to refuel at SPBU Pertamina 34.167.12. Simultaneously, service quality and brand image were found to significantly influence customer satisfaction. These findings provide guidance for other companies in the energy supply sector, particularly in the petroleum industry, in formulating strategies to improve customer satisfaction based on the results of this research.